PERLINDUNGAN HUKUM HAK ANAK SEBAGAI KORBAN EKSPLOITASI EKONOMI DALAM PERSPEKTIF HUKUM PIDANA DI KOTA PEKANBARU - Zuri Zuri; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Children who are victims of economic exploitation in Pekanbaru City. Crimes in community life that involve children are increasingly complex, with various behaviors, so there are various kids of crime so that legal protection is needed as an alkternative and enforcement so that life becomes orderly and comfortable. The majority of children who arevictims of economic exploitation are between the ages of 12 and 17 who are still in elementary school. The majority of children who are victims of economic exploitation in Pekanbaru City are used as beggars and sell late at night, causing an impact in the form of pressure for shildren to make income deposits, disruption of rest time and disruptiiion of playing timen and growth and development, this occurs due to circumstances economy is getting increasingly difficult so that there are children who deliberately take the initiative to help the family but by working with irregular and draining work schdules, but he majoryity of children are deliberately employed as bggars who are used by unscrupulous individuals including family experts and even their parents to get profit for the necessities of daily life without them having to work to support these children.This study aims to determine the legal protection of children who are victims of economic exploitation in Pekanbaru City which is carries out by the Pekanbaru City goverment through the social serrvice and related local goverments based on field studies and interviews. This type of reseach is categorized into a socialogical legal research which originates from factual events and problems that occur and develop in the midset of society, especially in Pekanbaru City.The results of this study are three important things, firstly it intends to comply with the extent of legal protection that has been carried out by the Pekanbaru City goverment in term of protecting the right of victims who are economically exploited in Pekanbaru City. Second, what efforts can the goverment of Pekanbaru City do in fighting the crime of economic exploitation of children who are turned beggars. Keyword: Protection Law, Victims, Children, Economis Exploitation